Valproic acid, a molecular lead to multiple regulatory pathways - Kostrouchová, M; Kostrouch, Z; Kostrouchová, M (Folia biologica, 2007)
Valproic acid (2-propyl pentanoic acid) is a drug used for the treatment of epilepsy and bipolar disorder. Although very rare, side effects such as spina bifida and other defects of neural tube closure indicate that valproic acid interferes with developmental regulatory pathways. Recently obtained data show that valproic acid affects cell growth, differentiation, apoptosis and immunogenicity of cultured cancer cells and tumours. Focused studies uncovered the potential of valproic acid to interfere with multiple regulatory mechanisms including histone deacetylases, GSK3 alpha and beta, Akt, the ERK pathway, the phosphoinositol pathway, the tricarboxylic acid cycle, GABA, and the OXPHOS system. Valproic acid is emerging as a potential anticancer drug and may also serve as a molecular lead that can help design drugs with more specific and more potent effects on the one side and drugs with wide additive but weaker effects on the other. Valproic acid is thus a powerful molecular tool for better understanding and therapeutic targeting of pathways that regulate the behaviour of cancer cells.
Keywords: Neoplasms; regulace genové exprese u nádorů; kyselina valproová; nádory; protokoly protinádorové kombinované chemoterapie; Animals; Gene Expression Regulation, Neoplastic; lidé; zvířata; Teratogens; Antineoplastic Agents; protinádorové látky; teratogeny; Valproic Acid; Antineoplastic Combined Chemotherapy Protocols; Humans